EFEKTIFITAS FUNGSI PENGAWASAN DEWAN PERWAKILAN RAKYAT DAERAH (DPRD) DALAM PENANGGULANGAN KORUPSI YANG DILAKUKAN OLEH APARATUR SIPIL NEGARA (ASN) (STUDI di DPRD KOTA MALANG) - Waode Daen Siti Nurcahya Ningsi (Pascasarjana Ilmu Hukum, Universitas Widyagama Malang, 2017)
Decentralization policy is aimed at realizing regional independence. Autonomous regional governments have the power to organize and manage the interests of local communities according to their own initiative based on the aspirations of the people. To implement autonomy, regional legislation should not conflict with the legal principles of a unitary state and society. Therefore, it is necessary that the DPRD to supervise it as a function of its supervision. The incidents of various corruption cases that one of the perpetrators is the State Apparatus indicate the absence of effective oversight of the DPRD in the handling of corruption committed by the State Civilian Apparatus. This is due to weak supervision from both the institution and the DPRD itself, so that the effectiveness of the DPRD oversight function in the handling of corruption conducted by the State Civil Apparatus is still weak or ineffective. Keywords: Decentralization and Regional Autonomy, Supervision, Supervision Function of District / City DPRD, Corruption